Scientometric Analysis on Cash Waqf Linked Sukuk (CWLS) - Aam Slamet Rusydiana; Mia Sari; Siti Maysyaroh (Islamic Economics Methodology, 2023)
This study aims to conduct a scientometric analysis of the literature related to Cash Waqf Linked Sukuk (CWLS) in the context of waqf. The scientometric method is used to measure and analyze the development patterns, research contributions, and interactions between researchers in the CWLS domain. Data was collected through the scientific literature platform Dimensions.ai with relevant keywords. Data visualization was also used to understand the relationship between authors, publications, and key concepts in CWLS literature. The results of this analysis provide insights into the development of research, key contributions of researchers, as well as the evolution of concepts in CWLS. This study provides a more comprehensive view through research paths with specific theme clusters of the CWLS-related literature and helps identify key patterns and important contributions in understanding the implications of Islamic economics and finance in the context of waqf.